Perspektif Penerapan Sanksi Pidana Atas Kerugian Keuangan Negara dalam Tindak Pidana Korupsi - Munsen Bona Pakpahan; Fajar Fajar; Agustin Agustin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The application of main and additional criminal witnesses in the PTPK Law has become firm with the existence of legal norms for the return of state financial losses that do not eliminate the criminalization of the perpetrators of criminal acts but only factors that alleviate punishment. This is important so that there is no disparity in punishment. And likewise punish paying restitution if the act is committed jointly, so that a sense of justice occurs,The research method used is normative juridical. Which type of data used is primair legal material obtained from all publications on law, literature that is not an official document. Publications about the law include, among others, the internet, textbooks, law journals, articles, comments, court regulations and other sources; The types of criminal sanctions in the PTPK Law, namely in the form of principal punishment and additional punishment in the form of restitution, are closely related. Aspects of the amount of state financial losses, aspects of the perpetrator's guilt, aspects of the benefits obtained by the perpetrator, the impact caused by the perpetrator and the return of losses made by the perpetrator. Such is the case in imposing additional punishment in the form of paying restitution. In the PTPK Law, the amount of restitution is interpreted as “not merely assessing state financial losses, but assessing how much money is actually received by the perpetrator”, so that the imposition of restitution is in accordance with objective and proportional principles. Likewise, the imposition of restitution in the case of corruption crimes committed jointly and tried simultaneously, the additional restitution cannot be imposed jointly.